Menstrual Hygiene Management During Emergencies: A Study of Challenges Faced by Women and Adolescent Girls Living in Flood-prone Districts in Assam. (February 2019) - Bhattacharjee, Mayuri
Women and adolescent girls in disaster-prone and fragile contexts face many challenges. This study 1 brings out various cultural and logistical issues faced by women and adolescent girls in taking care of their menstrual hygiene needs during floods. Data were collected in the flood-prone state of Assam from village communities in three districts—Sonitpur, Biswanath and Nagaon—through semi-structured interviews, focus group discussions and observations. Although sanitary napkins were distributed in some situations, there seemed to be no strategic plan or prior preparation for disposal despite the fact that floods are an annual occurrence in Assam. The absence of separate toilet facilities and disposal systems for menstrual waste were some of the key challenges faced by women and adolescent girls in relief camps or temporary shelters. Although there are disaster management guidelines on gender-sensitive and inclusive water, sanitation and hygiene response, humanitarian agencies including the state departments are yet to adopt them during the annual floods in Assam.